2020
DOI: 10.1097/sap.0000000000002171
|View full text |Cite|
|
Sign up to set email alerts
|

Attitudes of Hand Surgeons and Hand Reconstruction Patients Toward Hand Allotransplantation in Taiwan

Abstract: Background Recent advances in immunosuppressive protocols have increasingly made hand allotransplantation a realistic reconstructive option with more than 100 cases performed worldwide. While attitudes toward allotransplantation have been assessed for North American surgeons and patients alike, similar assessments have previously remained unconducted in Asia in general and Taiwan in specific. This study examines the perceptions of both Taiwanese hand surgeons and hand reconstruction patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The field of HT is exceptionally dynamic and scientific advancement will inevitably drive changes in eligibility criteria, one past example is the age of eligibility. Historically, most centers placed strict age Akdeniz University Hospital 15,16 Antalya, Turkey 2021 Amrita Institute of Medical Sciences 17,18 Kochi, India 2017 Boston Children's Hospital 19 Boston, MA 2022 Brigham and Women's Hospital [20][21][22][23][24][25][26][27] Boston, United States 2011-2022 Chang Gung Memorial Hospital [28][29][30][31] Children's Hospital of Philadelphia 5,[32][33][34][35][36] Taipei, Taiwan Philadelphia, PA 2016-2020 2016-2022 Clinica Cavadas [37][38][39][40][41] Valencia, Spain 2009, 2011 Duke University [42][43][44][45][46][47][48][49] Durham, USA 2011, 2018, 2021, 2022 Emory University 50,51 Atlanta, United States 2015 Hacettepe University 52 Ankara, Turkey 2014 Harbin Medical University 53 Harbin, China 2016 Hôpital Edouard Herriot 9,[54][55]…”
Section: Discussionmentioning
confidence: 99%
“…The field of HT is exceptionally dynamic and scientific advancement will inevitably drive changes in eligibility criteria, one past example is the age of eligibility. Historically, most centers placed strict age Akdeniz University Hospital 15,16 Antalya, Turkey 2021 Amrita Institute of Medical Sciences 17,18 Kochi, India 2017 Boston Children's Hospital 19 Boston, MA 2022 Brigham and Women's Hospital [20][21][22][23][24][25][26][27] Boston, United States 2011-2022 Chang Gung Memorial Hospital [28][29][30][31] Children's Hospital of Philadelphia 5,[32][33][34][35][36] Taipei, Taiwan Philadelphia, PA 2016-2020 2016-2022 Clinica Cavadas [37][38][39][40][41] Valencia, Spain 2009, 2011 Duke University [42][43][44][45][46][47][48][49] Durham, USA 2011, 2018, 2021, 2022 Emory University 50,51 Atlanta, United States 2015 Hacettepe University 52 Ankara, Turkey 2014 Harbin Medical University 53 Harbin, China 2016 Hôpital Edouard Herriot 9,[54][55]…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to previously reported data from Taiwan whereby 66 percent of patients with replantation procedures considered bilateral amputation to be an indication for hand transplantation as opposed to 27 percent for unilateral nondominant hand amputation. 34…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to previously reported data from Taiwan whereby 66 percent of patients with replantation procedures considered bilateral amputation to be an indication for hand transplantation as opposed to 27 percent for unilateral nondominant hand amputation. 34 Because health utility outcome measures are dependent on certain assumptions and scenarios, some limitations of this study need to be addressed. First, none of the patients with unilateral or bilateral amputations have been offered the possibility of undergoing a hand transplantation in our province, whereas some have been exposed to some degree to upper extremity prostheses (mostly body-powered) as part of their rehabilitation program.…”
Section: Ementioning
confidence: 99%
“…As the decision to undergo a hand transplant carries a significant psychological burden, medical advancements should be paralleled by studies that delineate treatment preferences to provide high-quality patient-centered care 40–43 . Previous studies have found that only 15% to 40% of surgeons support performing a hand transplant with currently available immunosuppression regimens 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…As the decision to undergo a hand transplant carries a significant psychological burden, medical advancements should be paralleled by studies that delineate treatment preferences to provide high-quality patient-centered care. [40][41][42][43] Previous studies have found that only 15% to 40% of surgeons support performing a hand transplant with currently available immunosuppression regimens. 40,41 However, as vascularized composite tissue allotransplantations transforms into a clinical reality, 44,45 few studies have attempted to clarify treatment preferences when weighing the risk-benefit ratio of a prosthetic or transplanted hand.…”
Section: Discussionmentioning
confidence: 99%